2019
DOI: 10.1021/acs.accounts.9b00412
|View full text |Cite
|
Sign up to set email alerts
|

The Fundamentals Behind the Use of Flow Reactors in Electrochemistry

Abstract: ConspectusIn the past decade, research into continuous-flow chemistry has gained a lot of traction among researchers in both academia and industry. Especially, microreactors have received a plethora of attention due to the increased mass and heat transfer characteristics, the possibility to increase process safety, and the potential to implement automation protocols and process analytical technology. Taking advantage of these aspects, chemists and chemical engineers have capitalized on expanding the chemical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
249
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 429 publications
(253 citation statements)
references
References 54 publications
2
249
0
2
Order By: Relevance
“…Typically, the electrode size is increased and larger amounts of supporting electrolyte are required to cope with the increase in Ohmic drop. Therefore, nearly all industrial electrochemical processes are carried out as flow processes in narrow-gap cells (inter-electrode gap = 0.5-10 mm) which are numberedup depending on the targeted throughput [16]. As can be seen from Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, the electrode size is increased and larger amounts of supporting electrolyte are required to cope with the increase in Ohmic drop. Therefore, nearly all industrial electrochemical processes are carried out as flow processes in narrow-gap cells (inter-electrode gap = 0.5-10 mm) which are numberedup depending on the targeted throughput [16]. As can be seen from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Biphasic reaction conditions (acetonitrile/1 M HCl) are required and the reaction was carried out in batch. However, preliminary studies showed that the use of flow chemistry was of great benefit [16][17][18][19][20]. The reaction time could be reduced to the minute range in flow and no mass transfer limitations were observed.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to reduced waste generation, the atom economy of electrochemical methods is most often superior to conventional procedures. The resurgence of organic electrochemistry has been accompanied by an increased attention to flow electrochemistry [6][7][8][9][10]. Implementation of flow cells is widely recognized as the appropriate method for the scale-up of electrochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Flow cells typically consist of two flat electrodes placed in parallel with a narrow distance (< 1 mm) between them [6][7][8][9][10]. The solution of reactants solution is then flown through the gap, where the electrolysis occurs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation